Science Meets Politics: Machiavelli's Influence and the Birth of Political Science - Almási, Gábor, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
Machiavelli's early influence was more penetrating than has ever been believed, and this book explains why. The surprising answer leads the reader into the depths of the history of science, connecting Machiavelli's thought to new ways of thinking about experience, history, nature, and politics. Machiavelli's works resonated with readers not merely because of the political and moral questions they raised and answered, and this book argues that the ways in which Machiavelli engaged with these questions were of equal importance. His method reinforced the readers' own belief in the importance of an inductive and comparative approach, which relied on facts and numbers drawn from history and experience.